Implementation of a smart microgrid in a small museum: the silk house - Figueiredo, Luís Guilherme Aguiar (2020)
Microgrids are an alternative approach for the supply of energy integrating decentralized power sources, electrical loads, energy storage, and management in a local grid. The system has the capability of power control and energy management using communications’ network between all devices, and is known as smart microgrid. This paper presents the implementation of a smart microgrid in the Silk House, a museum dedicated to dissemination of science located in Bragança, Portugal. It was funded by the Foundation for Science and Technology of Portugal under the SilkHouse Project. The goal is to transform the House of Silk in a self-sustainable museum contributing to the dissemination of renewable sources and new technologies for future buildings in smart cities. This work presents the context and requirements for the microgrid and describes the implementation of the renewable sources (photovoltaic and pico-hydro) and the SMA Flexible Storage System based on Sunny Island and Sunny Home Manager. This work also presents and analysis the first operating results since the start of operation at the end of July 2019.